2021
DOI: 10.26873/svr-1205-2021
|View full text |Cite
|
Sign up to set email alerts
|

THE FIRST OUTBREAK OF VIRAL ENCEPHALOPATHY AND RETINOPATHY IN FARMED SEA BASS (Dicentrarchus labrax) IN SLOVENIA

Abstract: Viral encephalopathy and retinopathy (VER) is considered a serious disease of several marine fish species, caused by RNA virus belonging to the family Nodaviridae, genus Betanodavirus. The disease is spread almost worldwide and causes significant losses among diseased fish. It is characterised by vacuolation of the central nervous system and the retina. In July 2018, behavioural abnormalities i.e. altered swimming, swirling and vertical floating as well as lethargy and anorexia were observed in farmed sea bass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The retina and central nervous system, including the brain and spinal cord, are the target organs of the NNV (Bovo et al 2011 ). The kidney, spleen, and heart are not considered target organs and are therefore unsuitable for NNV diagnosis; however, the causative agent of the disease can be detected in many organs (Sitar et al 2021 ). Our results revealed that the kidney, heart, and spleen tissues could be suitable for virus analysis, in addition to the eye and brain (Sitar et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retina and central nervous system, including the brain and spinal cord, are the target organs of the NNV (Bovo et al 2011 ). The kidney, spleen, and heart are not considered target organs and are therefore unsuitable for NNV diagnosis; however, the causative agent of the disease can be detected in many organs (Sitar et al 2021 ). Our results revealed that the kidney, heart, and spleen tissues could be suitable for virus analysis, in addition to the eye and brain (Sitar et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The kidney, spleen, and heart are not considered target organs and are therefore unsuitable for NNV diagnosis; however, the causative agent of the disease can be detected in many organs (Sitar et al 2021 ). Our results revealed that the kidney, heart, and spleen tissues could be suitable for virus analysis, in addition to the eye and brain (Sitar et al 2021 ). NNV can remain infectious at various temperatures (Binesh and Greeshma 2013 ).…”
Section: Discussionmentioning
confidence: 99%